The Compulsory Addition in Arabic Morphological Formulas - Al-Waeli, Batoul Abbas Naseem (Arab Journal for Sciences and Research Publishing, 2017)
What attracts attention is that there is some compulsory addition in some Arabic morphological formulas, which arefew compared to the non-compulsory addition known and limited in certain words and phrases, which prompts those whosearch it to submit a set of questions, the most important of which are:1. What is the definition of the compulsory addition?2. What are its characteristics?3. How to distinguish between compulsory and non-compulsory addition?This research is able to answer these questions, and it came as follows:- A Preface which presents compulsory addition linguistically.- The first topic defines the compulsory addition in terminology.- The second topic is about the characteristics of the compulsory addition and its origins.- The third topic: About the compulsory addition in the Arab morphological formulas.- The conclusion: An emphasis on the main findings of the research.
Keywords: increase; necessary